PERBANDINGAN PENDIDIKAN - Abdul Wahab Syakhrani; Enjelina Enjelina; Hervina Indah Putri; Jamiatur Rasidah; Nikmatul Bolqiah (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
Based on the explanation above, we can conclude that: 1) Comparative education is a comparative study (comparative study) on education, or a study of education using comparative approaches and methods. 2) The purpose of comparative education as a whole is to find the advantages of education in a place and improve education that is lacking. 3) Educational comparative methods are historical, descriptive, statistical, philosophical, comparative and quasi-experimental. 4) The scope of educational comparison is about administration, curriculum, learning schedules, learning methods, etc.